From Functional Grammar and Speech-Act Theory to Structure of Meaning: A Three-Dimensional Perspective on Translating - Zhu, Chunshen (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe article holds that textual comparison is of vital importance in translation studies. One of the key issues therefore is to identify the textual properties that are comparable and should be compared. In its investigation into the tri-stratal nature of language use in text formation, the article starts with a comparison of functional grammar and speech act theory. The investigation has led to a perception that textual meaning is a three-dimensional structure and hence to the production of a more comprehensive model, Structure of Meaning (SOM). The model is meant to offer a functional perspective on text formation in the process of translating, on a comparative basis, by examining one by one the three constituent dimensions, i.e., linguistic composition, interactional dynamic and aesthetic impact. The observation of proportionate relationships between the three dimensions of a Structure of Meaning has thrown some new light on issues such as genre, form and content, information, and effect, in the formation of the target language text.